CAR Peer Learning Guide. Issue 3 (August 2022) - Torres, Felipe Soares; Costa, Andreu F.; Kagoma, Yoan K.; Arrigan, Martin; Scott, Malcolm; Yemen, Brian; Hurrell, Casey; Kielar, Ania
Peer learning is a quality initiative used to identify potential areas of practice improvement, both on a patient level and on a systemic level. Opportunities for peer learning include review of prior imaging studies, evaluation of cases from multidisciplinary case conferences, and review of radiology trainees' call cases. Peer learning is non-punitive and focuses on promoting life-long learning. It seeks to identify and disseminate learning opportunities and areas for systems improvement compared to traditional peer review. Learning opportunities arise from peer learning through both individual communication of cases reviewed for routine work, as well as through anonymous presentation of aggregate cases in an educational format. In conjunction with other tools such as root cause analysis, peer learning can be used to guide future practice improvement opportunities. This guide provides definitions of terms and a synthetic evidence review regarding peer review and peer learning, as well as medicolegal and jurisdictional considerations. Important aspects of what makes an effective peer learning program and best practices for implementing such a program are presented. The guide is intended to be a living document that will be updated regularly as new data emerges and peer learning continues to evolve in radiology practices.